Enrolment, Attendance, and Education Resourcing and Support among 5-12 year old Autistic Students in Aotearoa New Zealand: A Nationwide Cross-sectional Study - Bowden, Nick; Anns, Francesca; Clendon, Sally; Dacombe, Joanne; Meehan, Lisa; Vu, Hien; Woodford, Emma; McLay, Laurie (International Journal of Population Data Science, 2026)
Introduction Participation in education underpins positive lifelong outcomes, yet Autistic children often encounter barriers to enrolment, attendance, and access to support. Evidence indicates that systemic challenges such as inadequate support, limited autism-specific teacher training, and restricted access to resources contribute to disparities in educational outcomes. While small sample studies highlight these inequities, population-level evidence is limited. Objectives To quantify nationwide differences in school enrolment, attendance, and access to educational resourcing and support services between Autistic and non-Autistic children aged 5–12 years in Aotearoa New Zealand (NZ), and to examine variation by co-occurring intellectual disability (ID). Methods Cross-sectional analysis using NZ's Integrated Data Infrastructure, including all children aged 5–12 in 2019. Autism and ID were identified from hospital, mental health, and disability service use datasets. Outcomes included enrolment, attendance, and access to supports. Propensity score matching (1:10) compared Autistic and non-Autistic students across outcomes, including stratification by ID status. Results Among 517,872 students aged 5-12 years, 8,169 (1.6%) were Autistic and of those 28.8% had co-occurring ID. Compared to matched peers, Autistic children were less likely to be enrolled in school (94.9% vs. 97.4%; Prevalence ratio [PR]=0.97, 95% confidence interval [CI]=0.97-0.98) but more likely to be enrolled in specialist schools (14.4% vs. 0.2%; PR=70.15, 95% CI=65.73-74.88), Te Kura (2.1% vs. 0.2%; PR=9.65, 95% CI=8.22-11.34), or home-schooling (2.2% vs. 0.9%; PR=2.45, 95% CI=2.11-2.84). Regular attendance was lower (49.3% vs. 61.2; PR=0.80, 95% CI=0.79-0.82), with higher rates of chronic absence (7.7% vs. 3.2%; PR=2.45, 95% CI=2.27-2.64). Access to supports was significantly higher for Autistic students across a range of services. Disparities were often more pronounced among Autistic children with ID. Conclusion This study demonstrates significant differences in enrolment, attendance, and access to educational supports between Autistic and non-Autistic students in NZ, underscoring the urgent need for targeted and sufficiently resourced supports to ensure equitable participation.